The relationship between work stress and quality life among Indonesian health workers during the COVID-19 pandemic - Yustina P. M. Paschalia; Anatolia K. Doondori; Theresia Avila Kurnia; Bonaventura R. Seto Se (Public Health of Indonesia)
Background: During the COVID-19 pandemic, health workers are directly involved in many healthcare activities. If the pandemic lasts for a long time, the situation of ambiguity and full of threats will be unimaginable. It will potentially worsen individual emotions, increase work stress, and affect the quality of life of health workers.